Formulating orange oil-in-water beverage emulsions for effective delivery of bioactives: Improvements in chemical stability, antioxidant activity and gastrointestinal fate of lycopene using carrier oils. (April 2018) - Meroni, Erika; Raikos, Vassilios
Abstract: The influence of carrier oil type on the chemical stability, antioxidant properties and bioaccessibility of lycopene in orange oil-in-water beverage emulsions was investigated. The emulsions were formulated with orange oil (A), which was partially (50%) replaced with tributyrin (B) or corn oil (C) because of their distinctively different fatty acid composition. The addition of corn oil enhanced the physical stability of the beverage during chilled storage by inhibiting Ostwald ripening. The formation of oxidation products was insignificant after storage for 28 days at 4 °C, regardless the type of added oil. Lycopene was more susceptible to chemical degradation in the presence of unsaturated, long chain triglycerides and the retention followed the order: A (87.94%), B (64.41%) and C (57.39%). Interestingly, bioaccessibility of lycopene was significantly lower for emulsions formulated with 50% corn oil as opposed to 100% orange oil as indicated by the simulated in vitro gastric digestion model. Graphical abstract: Unlabelled Image Highlights: Lycopene was encapsulated in beverage emulsions with different carrier oil. Beverages formulated with 50% LCT (corn oil) were physically stable. Lycopene was more susceptible to degradation in the presence of corn oil. The formation of oxidation products at the end of storage was insignificant. Bioaccessibility of lycopene decreased with the inclusion of LCT.